Blaski i cienie życia dorosłej osoby ociemniałej w kontekście przystosowania się do niepełnosprawności. Studium przypadku - Sokołowska-Kasperiuk, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
The article contains the information about diagnostic and functional differences between people blind from the birth and who lost sight during their lives. There are also described some functional consequentions of visual disability. The basic aim of the article is showing the psychological, social and physical situation of a blind person. The author uses examples from life of a particular person in a context of the process of adaption to disability (a case study).